Drug Resistance Associated with Blood Borne Bacteria in Dhaka Metropolis (Bangladesh Journal of Microbiology, 2019)
Blood borne infections are easy to contract during hospital procedures and can easily be transferred to other personnel in a healthcare setting. Bacteremia has become a common incidence and treatment is by administration of antibiotics. But this is not a simple task any more, since the pathogenic bacteria causing bacteremia are becoming resistant to a wide range of antibiotics. Blood samples were collected from outdoor patients seeking laboratory tests in Dhaka city. Blood samples were inoculated onto blood agar medium and after incubation for 37oC for 24 hours, bacterial isolates were identified and subjected to antibiotic susceptibility test by following the Kirby-Bauer method. The current present study deals with 100 patients of bacteremia from whom 150 isolates of 15 different bacterial genera have been collected among which the most prominent bacteria were Staphylococcus spp. (51 isolates), Pseudomonas spp. (19 isolates) and Escherichia spp. (19 isolates). After the antibiotic susceptibility test it was found that all isolates were resistant to a number of commonly used antibiotics. Twenty eight different antibiotics were used for this study. All isolates showed resistance to CAR, ATM, TOB, CXM, FD, CL, CAZ, AMC. NET and CN showed the most effective results (can effectively clear 9 and 10 types of isolates respectively found in this study). New discovery of drugs to fight these resistant pathogens is needed. In the meantime, safe administration of drugs, handling patients with appropriate protective personal clothing and apparatus, proper waste disposal managements in the hospital should be maintained strictly.Bangladesh J Microbiol, Volume 35 Number 2 December 2018, pp 134-140